2017
DOI: 10.21315/aamj2017.22.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphism in Advertising: The Effect of Anthropomorphic Product Demonstration on Consumer Purchase Intention

Abstract: Anthropomorphism refers to the tendency to imbue the nonhuman objects with human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 37 publications
(75 reference statements)
1
15
0
Order By: Relevance
“…Marketing research has also shown that a highly anthropomorphized portrayal of an influenza drug fighting influenza virus led viewers to a stronger perception that they understood how the drug worked (actual comprehension was not assessed). This in turn led to an enhanced perception of the drug's efficacy (Laksmidewi et al, 2017).…”
Section: Potential Infl Uences Of Anthropomorphismmentioning
confidence: 99%
“…Marketing research has also shown that a highly anthropomorphized portrayal of an influenza drug fighting influenza virus led viewers to a stronger perception that they understood how the drug worked (actual comprehension was not assessed). This in turn led to an enhanced perception of the drug's efficacy (Laksmidewi et al, 2017).…”
Section: Potential Infl Uences Of Anthropomorphismmentioning
confidence: 99%
“…Therefore, to the employees of such companies, the agency of the leader is more important than his communion (relation of interdependence). Similar interdependence effect appears in the advertising context when the product promises to help the consumer achieve personal goals [ 87 , 89 ]. Even though these results do not pertain to technology acceptance, they reveal something about the specific nature of the agentic and communal content for social cognition.…”
Section: Introductionmentioning
confidence: 81%
“…Perception patterns of other people and perception patterns of technology may be quite similar because people are able to attribute mental states and traits to non-social objects and other non-human beings [89,[95][96][97][98]. Thus, we introduce a self-congruity effect to better understand valuation process which results in positive attitude towards product [90,99], brand trust and loyalty [100,101], and purchase intention [102][103][104].…”
Section: A Congruence Between Technology Presentation and Fundamentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it was evaluated more positively in terms of service performance (Laban & Araujo, 2020). Moreover, anthropomorphic cues were found to positively affect consumers' purchase intentions, attitudes, and brand liking when used for branding products (Delbaere et al, 2011;Hart & Royne, 2017;Laksmidewi et al, 2017).…”
Section: Anthropomorphic Cuesmentioning
confidence: 99%